Kontribusi Celebrity Worship terhadap Pembelian Impulsif Remaja Penggemar K-Pop - Tenga Araminta Nadia Riwu Kaho; R. Pasifikus Ch. Wijaya; Juliana M.Y. Benu (Peneliti.net, 2023)
The purpose of this study was to determine the dimensions of the absorption contribution of celebrity adoration to the impulsive buying behavior of young K-Pop fans, to determine the dimensions of the contribution of addiction to celebrity worship to the impulsive buying behavior of young K-Pop fans, to determine the contribution of absorption and addiction to celebrity worship. as a whole on the impulsive buying behavior of adolescent K-Pop fans. The population in this study is all K-popers in Indonesia with statistical results showing a proportion of 23% of the 100 million K-popers in the world. In this study using a non-probability sampling technique, namely purposive sampling. This type of research is quantitative. The research results show that celebrity worship behavior contributes to the impulsive buying behavior of young K-Pop fans with a sample of 258 teenagers spread across several islands in Indonesia. The absorption dimension contributed 32.5% to the impulsive buying behavior of young K-Pop fans while the addiction dimension contributed 30.7% to the impulsive buying behavior of young K-Pop fans. Celebrity worship uses the F test to see the overall effect on consumptive behavior, namely the celebrity worship variable (absorption and addiction) has a significant influence on adolescent impulsive buying behavior in purchasing products related to idols of 63.2% and the remaining 36.8 % influenced by other factors.